A Single-Cell Culture System for Dissecting Microenvironmental Signaling in Development and Disease of Cartilage Tissue - Tassey, Jade; Sarkar, Arijita; Van Handel, Ben; Lu, Jinxiu; Lee, Siyoung; Evseenko, Denis (Frontiers in Cell and Developmental Biology, 2021)
Cartilage tissue is comprised of extracellular matrix and chondrocytes, a cell type with very low cellular turnover in adults, providing limited capacity for regeneration. However, in development a significant number of chondrocytes actively proliferate and remodel the surrounding matrix. Uncoupling the microenvironmental influences that determine the balance between clonogenic potential and terminal differentiation of these cells is essential for the development of novel approaches for cartilage regeneration. Unfortunately, most of the existing methods are not applicable for the analysis of functional properties of chondrocytes at a single cell resolution. Here we demonstrate that a novel 3D culture method provides a long-term and permissive in vitro niche that selects for highly clonogenic, colony-forming chondrocytes which maintain cartilage-specific matrix production, thus recapitulating the in vivo niche. As a proof of concept, clonogenicity of Sox9IRES-EGFP mouse chondrocytes is almost exclusively found in the highest GFP+ fraction known to be enriched for chondrocyte progenitor cells. Although clonogenic chondrocytes are very rare in adult cartilage, we have optimized this system to support large, single cell-derived chondrogenic organoids with complex zonal architecture and robust chondrogenic phenotype from adult pig and human articular chondrocytes. Moreover, we have demonstrated that growth trajectory and matrix biosynthesis in these organoids respond to a pro-inflammatory environment. This culture method offers a robust, defined and controllable system that can be further used to interrogate the effects of various microenvironmental signals on chondrocytes, providing a high throughput platform to assess genetic and environmental factors in development and disease.